Efektivitas Edukasi Keperawatan Dalam Meningkatkan Kepatuhan Pengobatan Pada Pasien Penyakit Kronis - Ivan Hartati Hura; Leli Wartani Zai (CV. SINAR HOWUHOWU, 2026)
Chronic diseases are among the leading causes of morbidity and mortality worldwide and require long-term treatment as well as patient adherence to therapeutic regimens to achieve optimal health outcomes. However, medication adherence among patients with chronic diseases remains a significant challenge in healthcare services due to various factors, including inadequate knowledge, low motivation, treatment complexity, and limited social support. Nursing education is one of the interventions that can improve patients’ knowledge, awareness, and ability to manage their conditions independently. This study aimed to examine the effectiveness of nursing education in improving medication adherence among patients with chronic diseases through a literature review approach. Literature was searched through Google Scholar, PubMed, ScienceDirect, SpringerLink, and Garuda databases using keywords related to nursing education, medication adherence, and chronic diseases. The reviewed articles were published between 2016 and 2026 and met the predetermined inclusion and exclusion criteria. The findings indicate that nursing education has a positive effect on improving medication adherence among patients with chronic diseases. Various interventions, including individual counseling, group health education, educational media, and technology-based education, were found to enhance patients’ understanding of their diseases and treatment regimens. Educational interventions combined with continuous monitoring and family support produced more optimal outcomes in improving medication adherence. Therefore, nursing education can be recommended as an effective strategy to support treatment success, reduce the risk of complications, and improve the quality of life of patients with chronic diseases.